Simulation of Train-Turnout Coupled Dynamics Using a Multibody Simulation Software. (22nd July 2018) - Lau, Albert; Hoff, Inge
Abstract : With the advancements of computing power, multibody simulation (MBS) tool is used to study not only train dynamics but also more realistic phenomena such as train-track coupled dynamics. However, train-turnout coupled dynamics within MBS is still hard to be found. In this paper, a train-turnout coupled model methodology using a MBS tool GENSYS is presented. Dynamic track properties of a railway track are identified through numerical receptance test on a simple straight track model. After that, the identified dynamic track properties are adopted in a switch and crossing (turnout) to simulate train-turnout coupled dynamic interaction including parameters such as rail bending stiffness and sleeper mass variation along the turnout. The train-turnout coupled dynamic interaction is compared to the dynamic interaction simulated from a widely accepted moving mass train-turnout model. It is observed that the vertical and lateral normal forces for the new train-turnout coupled model and the conventional moving mass train-turnout model are in good agreement. In addition, the new train-turnout coupled model can provide additional track dynamics results. It is concluded that the train-turnout coupled model can provide a more realistic train-turnout dynamic interaction compared to the moving mass train-turnout model.